FRANCHISING CONTROL AND PERFORMANCE: A STUDY ON THE ORGANIZATIONAL PERFORMANCE EVALUATION ACTIVITIES CONDUCTED BY FRANCHISORS (REGE Revista de Gestão, 2016)
This study presents a research conducted with 63 franchisors and master-franchisees, with focus on the organizational performance evaluation of is business model. Franchisors provided information on the evaluation process they held the franchisee and self-owned units in Brazil. These collected data were analyzed based on existing theoretical models in literature about evaluation and organizational performance measurement. It was possible to note that part of franchisors do not have a formulated conception of evaluation, neither a clear notion on how to conduct this evaluation process. In this context, it can be noticed that performance evaluation is not sustained in the organization strategic alignment, but in the establishment of control points by the franchisor on the franchisee. These interests are often linked to the brand and the quality of the activities (operational and services). Finally, trust between franchisor and franchisees plays a central role to franchise performance evaluation, and its non-existence was evidenced as the main barrier for the franchising performance evaluation activities.